2022
DOI: 10.3390/foods11152260
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancement of the Perception of Saltiness by Odorants Selected from Chinese Douchi in Salt Solution

Abstract: Douchi is a traditional fermented soya bean product that is popular for its smelled saltiness and unique flavor. In order to look for the relationship between smelled saltiness of volatiles and their saltiness-enhancing properties, gas chromatography-olfactometry/associated taste was used to select odorants associated with saltiness in Yongchuan Douchi. The enhancement effects of saltiness intensity by selected odorants were further verified by sensory evaluation analyses of 2-alternative forced-choice and odo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…They have then individually tested the effect of compounds identified. 15,19 However, our results show for the first time the existence of possible interactions between aromatic compounds that result in a greater or lesser capacity to enhance salty taste. Thus, the presence of certain aromas in food matrices may modify the aromatic compounds' capacity to enhance taste.…”
Section: Comparison Of the Aromatic Profiles Of Spices And Their Rela...mentioning
confidence: 63%
“…They have then individually tested the effect of compounds identified. 15,19 However, our results show for the first time the existence of possible interactions between aromatic compounds that result in a greater or lesser capacity to enhance salty taste. Thus, the presence of certain aromas in food matrices may modify the aromatic compounds' capacity to enhance taste.…”
Section: Comparison Of the Aromatic Profiles Of Spices And Their Rela...mentioning
confidence: 63%
“…The screening of VOCs for sensory evaluation was based on two factors: (i) correlation with the contents of Na and K ions ( R > 0.75), (ii) correlation with the salty flavor ( R > 0.7). Previous literature has reported VOCs with salty enhancement. , Our aim was to compare the saltiness-enhancing ability of reported VOCs and VOCs identified in the present study. Finally, 16 VOCs were selected to study the retronasal odor-induced salty enhancement, including 4 pyrazines, 5 organic acids, 4 sulfur-containing compounds, and 3 other VOCs (Table ).…”
Section: Resultsmentioning
confidence: 88%
“…In order to study the dynamic change of saltiness intensity induced by different VOCs, time intensity (TI) tests were conducted during the oral processing process, including evaluation of the salty aftertaste for 50.0 s. Previous literature reported a variety of pyrazine compounds, such as 2,5-dimethylpyrazine and 2,6-dimethylpyrazine, showing good saltiness-enhancing effect, ,, but did not compare the dynamic changes of their saltiness. In our experiment, four pyrazine compounds A1, A2, A3, and A4 were used for TI evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Different previous studies confirmed the use of herbs and spices as an excellent strategy for the reduction of the salt amount in food products [ 8 , 9 , 37 , 38 ]. However, the use of aromatic herbs and spices is often associated to the culinary and cultural habits of subjects [ 3 , 10 ]. Moreover, it is important to note that the use of aromatic herbs and spices rich in phytochemicals with anti-inflammatory effects has also been demonstrated as a potential strategy for the treatment of hyposmia and ageusia [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the Mediterranean zone, different herbs and plants such as basil, bay, peppermint, rosemary, and sage are normally used to increase food flavor and taste perception [ 3 , 8 , 9 ]. Gao and Colleagues suggested the use of Chinese douche, a traditional fermented soya bean product, to improve salty taste and reduce the salt intake [ 10 ]. In our previous study [ 3 ], we confirmed the important role of Mediterranean aromatic plants (rosemary, myrtle, orange, and saffron) in the enhancement of salt perception and qualified the use of flavored sea salts as a potential strategy to reduce daily salt intake.…”
Section: Introductionmentioning
confidence: 99%